English Literature: An Authentic/Interesting Teaching/ Learning Material/Resource for English Language Development - Sharma, Raj Kumar (Journal of NELTA Karnali, 2022)
This study is focused on finding how English literature assists to ameliorate English language in English language teaching (ELT) class attempting to analyze how literature attunes students with various language skills in ELT classroom. Commencing with the debate about teaching English language whether using only exponents of English language or teaching English language through literature, it proposes to research on how English literature assists as both content and language for ELT. Furthermore, it quests to answer many queries concerned with the relationship between language and literature. The research project is library based research utilizes secondary source of required data. Regarding the debate on the basis of analysis and discussion of the secondary data, it is argued that as an authentic teaching and learning materials, literature imparts knowledge about language, cultural, and religion entertaining readers assists to ameliorate language skills and knowledge of culture and religion of the target language. So, understanding its authenticity, it is prescribed in ELT courses of Nepali universities under Bachelor and Masters of Education English program but that is limited portion. To increase learners’ awareness about language, culture, religion and philosophy, it seemed necessary to increase portion of literature in ELT courses. Furthermore, for effective learning, it is better to prioritize epali writers’ literary writing in English or their authentic translated versions from Nepali to English too.